Chile GEI Index: A Comparative Study in Latin America/Carribbean - Safitri, Dina (Universitas Nahdlatul Ulama Surabaya, 2024)
Entrepreneurship, widely acknowledged as pivotal for economic development, has spurred global interest among policymakers, prompting the formulation of policies aimed at fostering entrepreneurial activities. Entrepreneurs, driven by vision, innovate products, processes, and services, thereby stimulating economic growth, creating employment opportunities, and bridging the gap between invention and commercialization. As economies seek ways to accelerate employment and enhance productivity, entrepreneurship emerges as a potential solution, particularly for those grappling with prolonged economic crises. To better understand and improve entrepreneurial landscapes, scholars have developed measurement methods, with the Global Entrepreneurship Index (GEI) standing out as a comprehensive model. By blending entrepreneurship with institutional factors, GEI offers insights into a country's entrepreneurial ecosystem. It comprises three sub-indexes, each reflecting entrepreneurial attitudes, abilities, and aspirations, supported by 14 pillars and 28 variables. GEI recommends five levels of index building to gauge entrepreneurship at the national level. This study focuses on Chile's entrepreneurship profile, utilizing world data from GEI that available spanning 2015 to 2017. Chile, positioned 15th in the World GEI Index during this period, stands out as the only representative from South America/Latin America/Caribbean countries. Despite its economic strength and numerous trade agreements, Chile has room for improvement to bolster its regional standing. Entrepreneurship measurement methods encompass quantitative and qualitative approaches. While quantitative methods offer statistical insights, they may lack depth in understanding entrepreneurship's broader impact. Qualitative methods, in contrast, delve deeper into the correlation between entrepreneurship and economic development, emphasizing opportunity-driven entrepreneurship and innovation. GEI methodology offers a unique perspective, integrating institutional and cultural dimensions to assess entrepreneurship's role in economic development. Notably, GEI highlights the importance of addressing bottlenecks within entrepreneurial ecosystems, wherein the lowest-performing pillars impede overall progress. The Triple-A structure of GEI encompasses entrepreneurial attitudes, abilities, and aspirations, underpinned by 14 pillars reflecting both individual and institutional variables.